2013
DOI: 10.1186/1479-5868-10-9
|View full text |Cite
|
Sign up to set email alerts
|

Are screen-based sedentary behaviors longitudinally associated with dietary behaviors and leisure-time physical activity in the transition into adolescence?

Abstract: BackgroundThere is a need for more longitudinal studies investigating the associations between screen-based sedentary behaviors (SB), dietary behaviors and leisure-time physical activity (PA).MethodsIn the HEIA cohort study, 908 children were followed from age 11 to age 13 (September 2007 – May 2009). The children self-reported their intake of fruits, vegetables, soft drinks with sugar and snacks. TV/DVD use, computer/game use and leisure-time PA were also self-reported. Multilevel generalized linear mixed mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 34 publications
(49 reference statements)
6
49
1
1
Order By: Relevance
“…Moreover, a study that used data from PeNSE 2012 showed a poorer quality diet among girls compared with boys 30 , suggesting that Brazilian female adolescents are more exposed to inadequate food consumption 29,30 . The finding regarding the association gradient between a higher amount of time spent watching TV and more elevated consumption of sugar-rich food products among adolescents is also consistent with evidence from other studies 17,31,32,33,34 . Evidence suggests that behavioral risk factors, such as the habit of watching TV, or lengthy screen time, and inadequate food consumption, have an influence on one another, tending to coexist in the form of a cluster, resulting in added risk of the development of overweight and comorbidities 32 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, a study that used data from PeNSE 2012 showed a poorer quality diet among girls compared with boys 30 , suggesting that Brazilian female adolescents are more exposed to inadequate food consumption 29,30 . The finding regarding the association gradient between a higher amount of time spent watching TV and more elevated consumption of sugar-rich food products among adolescents is also consistent with evidence from other studies 17,31,32,33,34 . Evidence suggests that behavioral risk factors, such as the habit of watching TV, or lengthy screen time, and inadequate food consumption, have an influence on one another, tending to coexist in the form of a cluster, resulting in added risk of the development of overweight and comorbidities 32 .…”
Section: Discussionsupporting
confidence: 90%
“…Evidence suggests that behavioral risk factors, such as the habit of watching TV, or lengthy screen time, and inadequate food consumption, have an influence on one another, tending to coexist in the form of a cluster, resulting in added risk of the development of overweight and comorbidities 32 . This coexistence can be justified by the elevated exposure of adolescents with higher screen time to advertisements of food products with elevated calorie content, such as sweets and soft drinks, favoring the consumption of those food groups instead of products with less media exposure, such as fruits and vegetables 14,17,31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the methodological limitations of available studies, the changes in lifestyle during the last decades, for example, increased sedentary behaviour [25][26][27] and the steadily increasing consumption of convenience food, 28 are likely to have changed usual energy and macronutrient intakes over years. The limited studies available in children from European countries report decreasing trends for overall energy and fat intake and increasing trends for carbohydrate intake [29][30][31] or stable fat intakes.…”
Section: Introductionmentioning
confidence: 99%